Top of the Class: The Importance of Ordinal Rank - Richard Murphy; Felix Weinhardt (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper examines the long-run impact of ordinal rank during primary school on productivity using comprehensive English administrative data. Identification is obtained from variation in test score distributions across cohorts and subjects, such that the same score relative to the class mean can have different ranks. Conditional on cardinal measures of achievement, being ranked highly during primary school has large effects on secondary school achievement, with the impact of rank being more important for boys than girls. Using additional survey data we find that the development of confidence is the most likely mechanisms for this effect on task-specific productivity.
Keywords: I21; J24; M54; 330; rank; non-cognitive skills; peer effects; productivity